Assembling care: How nurses organise care in uncharted territory and in times of pandemic. Issue 8 (5th August 2022) - Kuijper, Syb; Felder, Martijn; Bal, Roland; Wallenburg, Iris
Abstract: This article draws on ethnographic research to conceptualise how nurses mobilise assemblages of caring to organise and deliver COVID care; particularly so by reorganising organisational infrastructures and practices of safe and good care. Based on participatory observations, interviews and nurse diaries, all collected during the early phase of the pandemic, the research shows how the organising work of nurses unfolds at different health‐care layers: in the daily care for patients and their families, in the coordination of care in and between hospitals, and at the level of the health‐care system. These findings contrast with the dominant pandemic‐image of nurses as 'heroes at the bedside', which fosters the classic and microlevel view of nursing and leaves the broader contribution of nurses to the pandemic unaddressed. Theoretically, the study adds to the literature on translational mobilisation and assemblage theory by focussing on the layered and often invisible organising work of nurses in health care.